EPISTIMOLOGI AD-DAKHIL DALAM TAFSIR AL-QUR’AN - Moh. Jufriyadi Sholeh; Abdul Muiz; Ghozi Mubarok (Reflektika, 2026)
This article aims to examine the epistemology of ad-dakhīl in Qur’anic exegesis by analyzing its concept, development, and role in the methodology of exegesis. This study employs a qualitative approach using library research. Data were obtained from various primary and secondary sources related to 'Ulūm al-Qur'ān and studies on ad-dakhīl, and were then analyzed using content analysis with an epistemological approach. The results of the study indicate that etymologically, ad-dakhīl means something that enters or infiltrates, whereas terminologically, it refers to various elements, traditions, or methods of exegesis that lack scientific legitimacy and contradict the valid principles of exegesis. This concept is the opposite of al-aṣīl, which refers to interpretation derived from the Qur’an, the Sunnah, valid traditions, as well as accountable linguistic principles and exegetical methodologies. The study of ad-dakhīl is essential as a critical tool for preserving the authenticity of Qur’anic exegesis, assessing the validity of sources, and developing an objective methodology of exegesis. Historically, the emergence of ad-dakhīl was influenced by the influx of Isrā'īliyyāt narratives, weak and fabricated hadiths, sectarian fanaticism, as well as political and ideological interests in the development of exegesis. Ad-dakhīl is classified into ad-dakhīl fī al-manqūl and ad-dakhīl fī al-ra'y, each of which has its own characteristics and forms of deviation. This study emphasizes that an understanding of the epistemology of ad-dakhīl serves as a crucial foundation for developing a systematic critique of exegesis and for preserving the authenticity of Qur’anic interpretation amid the dynamics of contemporary exegetical studies.